FORMULASI STRATEGI PEMASARAN DIGITAL BERBASIS ANALISIS SWOT PADA USAHA KRIYA KAYU DESA BUGEMAN SITUBONDO - Yudha Praja; Riska Ayu Pramesthi (Growth, 2026)
Micro, Small, and Medium Enterprises (MSMEs) specializing in woodcraft in Bugeman Village, Situbondo Regency, hold significant economic potential due to the utilization of high-quality teak wood and the aesthetic skills of local artisans. However, limited digital literacy causes these business owners to still rely on passive and conventional marketing methods, resulting in a narrow market reach. This study aims to analyze the competitive position of the woodcraft business using a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to formulate an adaptive digital marketing strategy. The method employed in this research is a comparative case study integrating the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. The analysis results indicate that although the business excels in material quality and artistic value, the lack of understanding regarding e-commerce and structured promotions remains a primary weakness. Based on the SWOT matrix, four main strategic pillars were formulated to accelerate the business scale: enhancing product finishing quality, diversifying into modern designs, accelerating digital marketing ("Go Digital") by leveraging social media (TikTok and Instagram) and e-commerce platforms (Shopee), and expanding strategic partnerships with local distributors. Through this strategic restructuring, Bugeman Village's woodcraft MSMEs are expected to expand their market reach and achieve sustainable business growth.